Converging Faith, Culture, and Nature: Tourism as a Pathway to Togetherness in Multi-Ethnic Lasem, Indonesia - Giyoto Giyoto; Muh. Yahya; Elen Inderasari; Siti Noor Fazelah Mohd Noor; Khoirul Adi Nur Alfisyahri (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
Promoting social togetherness through educational institutions in diverse societies often encounters heightened sensitivity and resistance due to differences in religion, belief, culture, environment, and language, compared to approaches rooted in public activities such as tourism. In Indonesia, many tourism attractions originated as places of worship located in culturally significant areas, where local belief systems shape social and cultural practices. This study investigates how values of togetherness are practically manifested at the intersection of belief, nature, and sociocultural patterns in a tourism industry of Rembang, Indonesia. Data were collected through interviews, observations, and documentation involving tourism practitioners, visitors, site caretakers, and local government officials. Triangulation was employed to ensure data saturation, and analysis was conducted ethnographically using Spradley’s domain analysis. The findings reveal that the convergence of religious beliefs, sociocultural activities, and natural attractions fosters social cohesion among individuals from diverse backgrounds. This intersection not only sustains mutual understanding and appreciation of differences but also contributes to social harmony in Lasem, Rembang, enabling respectful interaction within a multi-ethnic, multi-religious, and multi-racial community.